2009
DOI: 10.5293/ijfms.2009.2.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Francis Runners - Experiment and Numerical Simulation

Abstract: The present paper shows the results of numerical and experimental modal analyses of Francis runners, which were executed in air and in still water. In its first part this paper is focused on the numerical prediction of the model parameters by means of FEM and the validation of the FEM method. Influences of different geometries on modal parameters and frequency reduction ratio (FRR), which is the ratio of the natural frequencies in water and the corresponding natural frequencies in air, are investigated for two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…The main excitation forces generated while the machine was in operation were applied to the runner. This is known as dynamic behavior and it allows the structural response of the runner to be calculated [1,2]. The main dynamic forces that act on the runner are described below.…”
Section: Damage Descriptionmentioning
confidence: 99%
“…The main excitation forces generated while the machine was in operation were applied to the runner. This is known as dynamic behavior and it allows the structural response of the runner to be calculated [1,2]. The main dynamic forces that act on the runner are described below.…”
Section: Damage Descriptionmentioning
confidence: 99%
“…Other publications have presented detailed experimental and numerical analysis considering the effect of surrounding mass of water [5][6][7] but in a reduced scale model and without taking into account the boundary conditions of the casing. Other publications about dynamic behavior in Francis turbines [8] do not give details about the impeller response.…”
Section: Introductionmentioning
confidence: 99%
“…Current technology using Computational Fluid Dynamics (CFD) is capable of design optimization of the hydraulic turbines both statically and dynamically [5,6]. Fluid Structural Interaction (FSI) analysis is performed for the structural analysis of the runner after it is hydraulically designed [7,8].Wang et al [9] demonstrated that reducing comprehensively the number of runner blades can increase the turbine capacity and found 13 blades is the optimal choice for the case of a small hydropower plant.…”
Section: Introductionmentioning
confidence: 99%